CO2 methanation on Ru/TiO2 catalysts: On the effect of mixing anatase and rutile TiO2 supports - Kim, Ara; Debecker, Damien P.; Devred, François; Dubois, Vincent; Sanchez, Clément; Sassoye, Capucine (Applied catalysis. B, Environmental, 2018)
[Display omitted] •Activity of Ru/TiO2 methanation catalysts strongly depends on support structure.•Mixing anatase and rutile before calcination can promote higher activity.•Positive effect linked to RuO2 migration and epitaxial stabilization on rutile TiO2.•For thermally stable supports, pure rutile remains the best support. The high CO2 methanation activity of Ru/TiO2 catalysts prepared by mixing both anatase and rutile TiO2 as a support is described, focusing on mild reaction temperature (50–200°C). The specific catalyst design elucidated the impact of the support mixing. Pre-synthesized, monodispersed 2 nm-RuO2 nanoparticles were used to serve as precursors for active metallic Ru responsible for the CO2 hydrogenation reaction. Pure TiO2 supports with different crystallinity (anatase and rutile) were either prepared in the laboratory or obtained from commercial providers, mixed, and used as supports in different ratios. The mixing was also done at different stages of the catalyst preparation, i.e. before RuO2 deposition, before annealing or after annealing. Our study uncovers that the interaction between the RuO2 nanoparticles and the anatase and rutile TiO2 phase during the annealing step dictates the performance of the Ru/TiO2 methanation catalysts. In particular, when beneficial effects of support mixing are obtained, they can be correlated with RuO2 migration and stabilization over rutile TiO2 through epitaxial lattice matching. Also, support mixing can help prevent the sintering of the support and the trapping of the active phase in the bulk of the sintered support. On thermally stable TiO2 supports, however, it appears clearly that the sole presence of rutile TiO2 support is sufficient to stabilize Ru in its most active form and to prepare a catalyst with high specific activity.